Studies on active chemicals in the saliva of the rice brown planthopper (Nilaparvata lugens) that elicit the production of rice volatiles - DU Meng-hao; YAN Xing-cheng; LOU Yong-gen; CHENG Jia-an (浙江大学学报. 农业与生命科学版, 2005)
Active chemicals were found to be present in the rice brown planthopper Nilaparvata lugens head extract that induced rice plants to release volatiles attractive to Anagrus nilaparvatae, an egg parasitoid of N. lugens and were shown to belong mainly to proteins. The activity of the extract was lost when stored at －15-－20℃ for 72 days, but it was retained for at least 5 weeks. Among volatiles emitted from rice plants that were wounded and treated with either α-glucosidase, β-glucosidase, a-amylase, or β-amylase, which are the four main enzymes present in the saliva of N. lugens, only were volatiles emitted from β-glucosidase-treated plants capable of attracting the parasitoid. The parasitoid showed no preferences for volatiles released from N. lugens-damaged plants compared to those from plants that were wounded and treated with either N. lugens head extract, proteins isolated from the extract or β-glucosidase. Volatiles released from rice plants that were elicited by N. lugens head extract, proteins isolated from the extract or β-glucosidase were similar to those from N. lugens-infested plants. These results suggest an important role of proteins, especially β-glucosidase in the saliva of N. Lugens in the production of N. lugens-induced rice volatiles. The possible nature of the active chemicals in the saliva of N. lugens and the potential mechanism by which they induce volatiles production were discussed in the paper.